COASTAL STYLE SEBAGAI RUMAH PELEPAS PENAT - Aretha, Fabianty Edgar; Badriyah, Siti (Institut Seni Indonesia Surakarta, 2021)
Coastal Style or what is known as the Nautical Style is an interior design style that describes the atmosphere of the beach and the sea waves. The atmosphere of this beach is identical to its cool coloring, namely blue, green, and brown sand. This style is suitable to be applied in Indonesia with its tropical climate. However, usually Coastal Style is applied to houses on the coast. The interior design theme that describes this beach succeeds in making the room's atmosphere breezy, calm, and peaceful. The accessories and decoration factor for this marine theme also adds to the beach feel to the room. With a coastal design, a house feels like a private beach that can keep the mind away from feeling stressed, and saturated with the problems that come your way. Keywords : Style, Coastal, Nautical, Beach, Breezy.